Performance characteristics of thromboelastometry assays using incompletely filled and prolonged stored samples - Paarup, Helene M.; Rasmussen, Mads H.; Yazer, Mark H.; Sprogøe, Ulrik (Transfusion (Philadelphia, Pa.), 2020)
BACKGROUND Thromboelastometry (TEM) is often used to guide transfusion therapy in patients with massive bleeding. The effect of testing incompletely filled samples and those stored for a prolonged time at 4°C was investigated. METHODS Whole blood samples were collected from 15 healthy blood donors and were pooled according to ABO group. From these pools, aliquots were taken and diluted to produce final whole blood:citrate buffer ratios ranging from 90:10 (fully filled sample) to 40:60 (extremely under filled samples). These samples were then tested by EXTEM, INTEM, and FIBTEM on calibrated ROTEM delta machines. Separately, the four samples at 90:10 dilution were kept at 4°C for 16‐20 hours and then retested on the ROTEM machines. RESULTS All of the samples at the 90:10 and 80:20 (half‐filled sample) whole blood:citrate buffer dilutions demonstrated ROTEM parameters within their respective reference ranges, although the samples from the 80:20 dilution tended to demonstrate slightly longer or slower times, depending on each ROTEM parameter, compared to the completely filled samples. All of the samples with more dilute whole blood to citrate buffer ratios (i.e., 70:30 to 40:60) yielded abnormal TEM results. The TEM results for the 90:10 dilution samples exposed to 16‐20 hours of storage at 4°C were within the reference intervals. CONCLUSION Completely and half‐filled samples, and completely filled samples after prolonged cold storage, produced normal ROTEM results. Tubes that are less than half‐filled should not be used for ROTEM testing.